Synthesis of branched alkane fuel from biomass-derived methyl-ketones via self-aldol condensation and hydrodeoxygenation. (1st September 2021) - Feng, Shan; Zhang, Xinghua; Zhang, Qi; Liang, Yuan; Zhao, Xuelai; Wang, Chenguang; Ma, Longlong
Highlights: This work provided a promising route for the synthesis of jet fuel range alkanes from renewable biomass. 500-MgAl-O catalyst exhibited the highest catalytic activity in the self-aldol condensation of MIBK. The yield of MIBK condensation product (C12 oxygenate) was 70.3%. The hydrodeoxygenation products were highly branched alkanes with low freezing-points (<−60 °C). Abstract: Production of aviation fuel is promising but challenging in the field of biomass utilization. Here we proposed a route to produce highly branched alkanes by the self-aldol condensation of methyl isobutyl ketone (MIBK), followed by the one-step hydrodeoxygenation (HDO). The catalytic activities of magnesium-aluminum mixed oxides (MgAl-O) were carefully explored in the self-aldol condensation of MIBK using cyclohexane as the solvent. The basic sites with moderate and strong strength play a key role in the self-aldol condensation of methyl isobutyl ketone, which can capture α-H, promoting the aldol condensation. Under an optimal condition, the yield of condensation product C12 oxygenate is 70.3%. Furthermore, the regeneration ability of 500-MgAl-O catalyst is tested in the self-aldol condensation of MIBK. In addition, hydrodeoxygenation of condensation products was also conducted over 2 wt% Pd/HZSM-5 catalysts. These obtained HDO products are highly branched alkanes with low freezing point (<−60 °C).